Application of Multivariate Techniques in Horticulture Research-a Case Study of Apple Crop - Sharma, Anju; Mahajan, P. K.; Malhotra, R.; Belwal, O. K.; Sharma, Satish K. (International Journal of Bio-resource and Stress Management, 2018)
The present study deals with the usefulness of Principal Component Analysis and Factor Analysis for determining the relative contribution of morphological characters responsible in increasing the apple productivity. The three different apple producing locations of Himachal Pradesh, viz., Shimla, Kotkhai, and Theog were considered for the study. Four of the thirteen principal components explained around 75.40, 86.58 and 89.40% of the total variation at Shimla, Kotkhai and Theog locations, respectively. The first principal component may be interpreted as Plant Vigour and Yield Component. The second component may be termed as Volume and Spurs of Plant and Yield component, while Fruitfulness and Size of Tree may be regarded as the third principal component. Factor analysis grouped the thirteen morphological characters into three main factors. At Shimla location, the first factor (Plant vigour and yield), the second factor (Fruitfulness) and the third factor (Size of Tree and Fruit) explained 37.55%, 21.43% and 9.33% of the total variation, respectively. At Kotkhai location, 55.01%, 17.37% and 7.92 % of total variation was explained by the Plant Vigour and Plant Growth (first factor), Fruitfulness (second factor) and Yield and Plant Vigour (third factor) characters, respectively. Factor analysis of Theog location showed that the first factor i.e. Plant Vigour, second factor i.e. Fruitfulness and the third factor i.e. Yield and Plant Growth explained 60.00%, 13.14% and 9.44% of the total variation, respectively. Total variance explained collectively by three factors was observed to be 68.31%, 80.29%, and 82.58% at Shimla, Kotkhai and Theog locations respectively.